Communication barrier in family linked to increased risks for food insecurity among deaf people who use American Sign Language. Issue 5 (31st January 2018) - Kushalnagar, Poorna; Moreland, Christopher J; Simons, Abbi; Holcomb, Tara
Abstract: Objective: Food security is defined as being able to access enough food that will help maintain an active, healthy lifestyle for those living in a household. While there are no studies on food security issues among deaf people, research shows that communication barriers early in life are linked to poor physical and mental health outcomes. Childhood communication barriers may also risk later food insecurity. Design/Setting/Subjects: A single food security screener question found to have 82 % sensitivity in classifying families who are at risk for food insecurity was taken from the six-item US Household Food Security Survey Module. Questions related to food insecurity screener, depression diagnosis and retrospective communication experience were translated to American Sign Language and then included in an online survey. Over 600 deaf adult signers (18–95 years old) were recruited across the USA. Results: After adjusting for covariates, deaf adults who reported being able to understand little to none of what their caregiver said during their formative years were about five times more likely to often experience difficulty with making food last or finding money to buy more food, and were about three times more likely to sometimes experience this difficulty, compared with deaf adults who reported to being able to understand some to all of what their caregiver said. Conclusions: Our results have highlighted a marked risk for food insecurity and related outcomes among deaf people. This should raise serious concern among individuals who have the potential to effect change in deaf children's access to communication.